2017
DOI: 10.1002/ceas.12087
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Acculturative Stress of International Students in CACREP Programs

Abstract: International students enrolled in programs accredited by the Council for Accreditation of Counseling and Related Educational Programs provided acculturative stress and needs data. Acculturative stress was correlated with academic, social, language, and cultural needs. Furthermore, relationships were found between students’ types of needs. Implications are offered to help meet international students’ needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
(95 reference statements)
1
15
0
3
Order By: Relevance
“…In this context, language ability is considered as the most important determinant of students' ability to adjust to a new setting (Freeman, Nga, & Mathews, 2017). Language barriers in an academic environment can not only affect the educational performance of international students but also lower their interaction with fellows and teachers (Behl, Laux, Roseman, Tiamiyu, & Spann, 2017). But in universities in China, the language of instruction is Chinese, and very few local people have proficiency in speaking English.…”
Section: Communication Barriersmentioning
confidence: 99%
“…In this context, language ability is considered as the most important determinant of students' ability to adjust to a new setting (Freeman, Nga, & Mathews, 2017). Language barriers in an academic environment can not only affect the educational performance of international students but also lower their interaction with fellows and teachers (Behl, Laux, Roseman, Tiamiyu, & Spann, 2017). But in universities in China, the language of instruction is Chinese, and very few local people have proficiency in speaking English.…”
Section: Communication Barriersmentioning
confidence: 99%
“…The 2017 literature included a strong body of literature regarding multicultural considerations and experiences of counselor trainees. Specifically, these focused on protective and risk factors for students of color (Hipolito‐Delgado, Estrada, & Garcia, 2017), experiences of microaggressions within preparation programs (Smith, Chang, & Orr, 2017), experiences of international students in clinical courses (Park, Lee, & Wood, 2019), and needs and acculturative stress in international students (Behl, Laux, Roseman, Tiamiyu, & Spann, 2017). Researchers also explored experiences of African American students related to faith and lesbian, gay, bisexual, and transgender (LGBT) affirmation (J. R. A. Harris, Roberston, Jones, & Prado, 2017); attitudes toward transgender persons (Kanamori & Cornelius‐White, 2017); and perceptions of ethical referrals (Lloyd‐Hazlett, Hobbs, & Honderich, 2017).…”
Section: Understanding Stakeholdersmentioning
confidence: 99%
“…A review of the literature surprisingly revealed little to no studies on exploring international school counseling students' (ISCSs) development and experiences. None of the previous studies (Behl et al, 2017;Ng & Smith, 2009) about ICSs focused on ISCS. Ng and Smith's (2009) work mentioned the inclusion of four school counseling students in the sample for their study.…”
Section: Challenges Iscss Face In Us School Counseling Training Promentioning
confidence: 99%
“…Nevertheless, studies from related fields such as marriage and family therapy (Mittal & Wieling, 2006) and rehabilitation counseling programs (Zhu & Degeneffe, 2011) have investigated the challenges of international students. Additionally, Behl, Laux, Roseman, Tiamiyu, and Spann (2017) have examined the acculturative needs of international students in CACREP programs. A consistent theme in these studies points to the essence of personal, academic, social, and cultural support for international students in counseling programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation